Some issues of implementation of the basic principles Humanocentrism in the execution of state policies in the sphere of private law regulation - Танцюра, Олена Станіславівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article describes the main modern scientific views on the concept of man-centeredness. It is noted that the Ministry of Justice as a leading executive body and the «institution of justice» has a significant influence on the modern transformational processes of the domestic state-legal policy, including in the sphere of private law regulation. Also a conclusion was made about its role in the formation and implementation of the basic principles of human centeredness in the process of implementing state legal policy in the sphere of civil law relations.